Evaluating community care : services for people with learning difficulties - Wright, Ken. (Open University Press, 1994)
The evaluation framework. The policy background. Definition and methodology. Specific research dimensions and their measurement. Evidence and issues. Cost measurement in theory. Cost measurement in pratice.